An Analisys of Students’ Ability in Applying Simple Present Tense in Descriptive Text at SMP Swasta Cenderamata - sardo merti lilis; Nia Srilestari Berutu; Rohani Meldara Aritonang; Raptama Panggabean (English Language Teaching Prima Journal (ELT), 2019)
The aim of this research are to know the ability of students in applying simple present tense in descriptive text, to know the problem of the students in applying simple present tense in descriptive text. This research is classified in to qualitative research. The subject of this research was taking sample from SMP Swasta Cenderamata Medan in second grade, there were 20 students in the class. The result of students’ ability in applying simple present tense in descriptive text is 57,7. From the response of the students in questionnaire shown that twelve (60%) from 20 students said that they didn’t understand about simple present tense, (60%) from 20 students stated that simple present tense is difficult, (75%) from 20 students responded that any problem for them in applying simple present tense in descriptive text, (70%) from 20 students responded that to write simple present tense in descriptive text is difficult, and also twelve (60%) from 20 students said that they are not able to write simple present tense in descriptive text correctly